Salix gordejevii females exhibit more resistance against wind erosion than males under aeolian environment - Ma, Shaowei; Liu, Guohou; Wang, Lei; Liu, Guanzhi; Xu, Xiao (Frontiers in Plant Science, 2022)
Effects of wind erosion on growth and adaptability have been widely reported in many plants, but little attention has been paid to dioecious plants. Recent studies have shown that sex-specific responses to environmental changes in many plants exist. To explore sexual differences in response to wind erosion, female and male Salix gordejevii saplings growing on inter-dune land (no erosion) and on the windward slope of the dune (20cm wind erosion) in Hunshandake Sandy Land were chosen and their morphology, biomass and physiological traits were investigated, respectively. Wind erosion significantly reduced plant growth, biomass accumulation, gas exchange and chlorophyll fluorescence, and obviously disrupted osmotic regulation function and antioxidant enzyme system in both sexes, especially in males. Under wind erosion condition, females exhibited higher sapling height (SH), basal diameter (BD), leaf dry mass (LDM), root dry mass (RDM), total dry mass (TDM), root percentage in total dry mass, net photosynthesis rate (Pn), maximum efficiency of photosystem II (Fv/Fm), effective quantum yield of PSII (ΦPSII), relative water content (RWC) of leaves, superoxide dismutase (SOD) and peroxidase (POD) activities, but lower malondialdehyde (MDA), proline as well as soluble sugar content than did males. However, no significant sexual differences in most of these traits were observed under no erosion condition. Our results demonstrated that females possess a greater resistance to wind erosion than do males, with females having a better photosynthetic capacity, stronger water retention capacity and more efficient antioxidant system to alleviate negative effects caused by aeolian environment.